Subcutaneous ICD implantation in a patient with hypertrophic cardiomyopathy after transvenous ICD failure: A case report. Issue 1 (14th December 2017) - Baroni, Matteo; Cattafi, Giuseppe; Arupi, Michele; Paolucci, Marco; Pelenghi, Stefano; Lunati, Maurizio
Abstract: We describe the case of a patient with hypertrophic cardiomyopathy who experienced the failure of a transvenous implantable cardioverter defibrillator (T‐ICD) lead and the following inability of a second T‐ICD to convert a ventricular fibrillation. A subcutaneous ICD (S‐ICD) was finally implanted and was effective at defibrillation test.